2005
DOI: 10.1081/ada-200056813
|View full text |Cite
|
Sign up to set email alerts
|

Preventing Alcohol and Drug Exposed Births in Washington State: Intervention Findings From Three Parent-Child Assistance Program Sites

Abstract: Home visitation interventions show promise for helping at-risk mothers, yet few programs have been developed and evaluated specifically for alcohol and drug-abusing pregnant women. This study examines outcomes among 216 women enrolled in the Washington State Parent-Child Assistance Program, a three-year intervention program for women who abuse alcohol and drugs during an index pregnancy. Pretest-posttest comparison was made across three sites: the original demonstration (1991-1995), and the Seattle and Tacoma … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
58
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(60 citation statements)
references
References 34 publications
2
58
0
Order By: Relevance
“…The data presented in this study are from the Parent-Child Assistance Program (PCAP), a 3-year public health advocacy/case management intervention for women who abuse alcohol and/or drugs during pregnancy (Ernst et al 1999;Grant et al 1996Grant et al , 2003Grant et al , 2005. The PCAP model is based on relational theory that posits the critical importance of affirming, supportive relationships within the intervention setting (Amaro and Hardy-Fanta 1995).…”
Section: Overviewmentioning
confidence: 98%
“…The data presented in this study are from the Parent-Child Assistance Program (PCAP), a 3-year public health advocacy/case management intervention for women who abuse alcohol and/or drugs during pregnancy (Ernst et al 1999;Grant et al 1996Grant et al , 2003Grant et al , 2005. The PCAP model is based on relational theory that posits the critical importance of affirming, supportive relationships within the intervention setting (Amaro and Hardy-Fanta 1995).…”
Section: Overviewmentioning
confidence: 98%
“…The primary aim of the model is to prevent future alcohol and drug exposed births among high-risk mothers who have already delivered at least one exposed child. Research findings demonstrated the PCAP model's effectiveness Grant et al 2003Grant et al , 2005, and the Washington State legislature subsequently funded PCAP to develop sites in nine counties and on the Spokane Reservation, creating a capacity to serve nearly 700 families state-wide. The model has been replicated at numerous other sites in the United States and Canada, including the Alberta First Steps Program which was initially funded through Catholic Social Services Sign of Hope Campaign and the McDaniel Family Foundation, and later funded by Alberta Government Ministry of Children's Services.…”
Section: The Interventionmentioning
confidence: 97%
“…Grant et al [65] found improved outcomes in the areas of substance use, contraceptive use, use of medical and mental health services, and improvements in maintaining stable housing arrangements. In a related study, Denys et al [66] found that a similar mentoring program for parents with FASD [n=24] was effective in helping clients reduce their needs and achieve their goals, particularly in the areas of social problems, experience of abuse, housing, transportation, self-care, and health.…”
Section: Mentoring Supportsmentioning
confidence: 99%
“…Grant et al [65] examined a mentoring program for women with FASD [n=19] to help connect them with community resources, obtain formal diagnoses of FASD, and assist with parenting. Grant et al [65] found improved outcomes in the areas of substance use, contraceptive use, use of medical and mental health services, and improvements in maintaining stable housing arrangements.…”
Section: Mentoring Supportsmentioning
confidence: 99%